Constructing Local Religious Landscapes: Spatiotemporal Evolution of Tibetan Buddhist Temples in the Tibetan–Yi Corridor - Tianyi Min; Tong Zhang (Religions)
Situated in the mountainous and gorge-ridden region at the junction of the Tibet Autonomous Region, Sichuan Province, and Yunnan Province, the Tibetan–Yi Corridor is home to the Kham Tibetan area, one of China’s three traditional Tibetan areas. Tibetan Buddhism and the establishment of its temples in this region have evolved and propagated from nothing to a diverse landscape since the 8th century. Existing studies, however, have paid little attention to the intricate interplay between the formation of this sacred religious landscape and the specific geographic and sociocultural contexts in which it is situated. By taking temple architecture as a research vehicle, this study begins by extracting spatial data from historical GIS network data resources and 276 local gazetteers of 45 counties in the Tibetan–Yi Corridor. Secondly, it digitalizes and quantifies the geographic information, construction dates, sectarian affiliations, and sizes of 1479 Tibetan Buddhist temples in the region, establishing a database covering four historical periods. Finally, it employs GIS technology to visualize the spatial distribution of these temples, revealing their spatial and temporal patterns and evolution. From a religious geographical perspective, this study reconstructs the historical trajectories and diffusion patterns of the Nyingma, Kagyu, Sakya, Gelug, Jonang, and Bon sects in the Tibetan–Yi Corridor, revealing the complex interplay, succession, and ebb and flow of these sects over time. The research results show that the historical spread and development of Tibetan Buddhism in the Tibetan–Yi Corridor were influenced by a complex interplay of geographical, social, political, and economic factors, including the unique topography of the Qinghai–Tibet Plateau and Hengduan Mountains, the complex interplay of agriculture and pastoralism, the historical influence of dynastic changes and central government policies on border regions, and ancient pilgrimage and trade routes. At the same time, as a multi-ethnic region inhabited by over 20 minorities, including Tibetans, Yi, Qiang, Naxi, and Nu, the Tibetan–Yi Corridor has a cultural identity dominated by religion, which has become an important factor in maintaining multi-ethnic symbiosis throughout its history, highlighting the unique historical status and role of the Tibetan–Yi Corridor in the entire Tibetan Buddhist cultural circle.